Development and testing of Schisto and Ladders™, an innovative health educational game for control of schistosomiasis in schoolchildren - Ejike, Cynthia Uchechukwu (BMC Res Notes, 2017)
BACKGROUND: Schistosomiasis remains a public health problem in many regions of the world, including Nigeria. Current control strategy involves mass drug administration with praziquantel to the endemic population. To complement and sustain on-going preventive chemotherapy, we developed a health educational game named Schisto and Ladders™ and tested its potential for the control of schistosomiasis among schoolchildren living in Imala-Odo, a highly endemic community near Abeokuta, Nigeria. METHODS: One hundred school children were randomly selected and divided into intervention and control groups through balloting. Their knowledge, attitudes and practices (KAP) concerning schistosomiasis transmission, control and prevention were assessed using structured questionnaires. Schisto and Ladders™ game were given to the intervention group and the popular Snake and Ladders™ game to the control group. Both games were played for 2 months under the supervision of their class teachers. A post-KAP assessment was carried out in both groups, including focus group discussions (FGDs) to investigate knowledge and the impact of the games. RESULTS: Knowledge about urinary schistosomiasis and its transmission significantly improved (P = 0.000) in the intervention group (68.0%) compared to the control group (8.0%). FGDs showed that the frequency of visits to dam water also significantly reduced (P = 0.048) in the intervention group (18.0%) compared to the control group (40.0%). There was a significant increase in knowledge regarding risk behaviours, prevention and control of schistosomiasis among the intervention group, but no new knowledge gained in the control group. CONCLUSIONS: This study demonstrates the potential of the health education game Schisto and Ladders™ for teaching basic health education and promoting behavioural changes among schoolchildren in endemic communities.